2017
DOI: 10.1186/s12864-017-4135-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis provides clues to molecular mechanisms underlying blue-green eggshell color in the Jinding duck (Anas platyrhynchos)

Abstract: BackgroundIn birds, blue-green eggshell color (BGEC) is caused by biliverdin, a bile pigment derived from the degradation of heme and secreted in the eggshell by the shell gland. Functionally, BGEC might promote the paternal investment of males in the nest and eggs. However, little is known about its formation mechanisms. Jinding ducks (Anas platyrhynchos) are an ideal breed for research into the mechanisms, in which major birds lay BGEC eggs with minor individuals laying white eggs. Using this breed, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Regarding eggshell quality, previous studies have focused primarily on transcriptomic analysis in the uterus, which can reveal the molecular mechanisms that may cause laying hens with different eggshell quality [9,10]. For the eggshell color, Wang et al [11] conducted transcriptomic analysis to identify molecular factors affecting blue coloration in the uterus of duck with blue-green eggshells and reported a large difference in cholesterol biosynthesis and ion levels involved in the modulation of the transporting activity of bile pigment transporters. In laying hens, most of previous experiments have studied protoporphyrin IX (PP9) synthesis and transport to eggshells, specifically in the uterus because PP9 is the main pigment of brown color in eggshells and its synthesis and deposition occur in the uterine [12,13].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Regarding eggshell quality, previous studies have focused primarily on transcriptomic analysis in the uterus, which can reveal the molecular mechanisms that may cause laying hens with different eggshell quality [9,10]. For the eggshell color, Wang et al [11] conducted transcriptomic analysis to identify molecular factors affecting blue coloration in the uterus of duck with blue-green eggshells and reported a large difference in cholesterol biosynthesis and ion levels involved in the modulation of the transporting activity of bile pigment transporters. In laying hens, most of previous experiments have studied protoporphyrin IX (PP9) synthesis and transport to eggshells, specifically in the uterus because PP9 is the main pigment of brown color in eggshells and its synthesis and deposition occur in the uterine [12,13].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…To date, many studies have reported on transcriptome sequencing in ducks. It is being widely used in the studies on duck-pathogens [ 10 15 ], duck-phenotypes [ 16 , 17 ] and duck-performance interaction [ 18 ]. In 2013, Tang et al carried out transcriptome sequencing to explore and compare the gene expression patterns of normal and DHAV-3 infected duckling livers at 24 hours post-infection (hpi) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six libraries from each group ( n = 3) were sequenced. First, raw reads in FASTQ format were filtered to generate clean reads by removing reads containing adapters or ambiguous nucleotides and reads of low quality, as described by Wang et al (2017a). Then, the filtered reads were mapped to the chicken reference genome (Gallus_gallus-5.0) using the spliced mapping algorithm of Tophat (version 2.0.9) with no more than two mismatches.…”
Section: Methodsmentioning
confidence: 99%